Integração ensino - serviço: os olhares dos docentes e de uma equipe de saúde da família - Alves, Maria Izabel de Mendonça (2020)
This Undergraduate Thesis aims to get to know the knowledge of teachers and health professionals, who have been working together since 2015, in a teaching staff of assistance located in the third health district of the city of Maceió, capital of Alagoas, on the Integration Teaching Service. And learn through them too, how was the work before the integration between a private educational institution and the municipal government health department, and also to know how the community reacted to this partnership. This thesis is a descriptive study, with qualitative emphasis, carried out in conjunction with the service team involved in the teaching-service integration process. In order to know the profile of this sample, 34 characterization questionnaires were applied, 15 for teachers and 19 for municipal government employees. The individual interview technique was used as a data collection tool and was carried out with 9 teachers and 10 municipal government employees, all performed after the analysis and application of the inclusion and exclusion criteria. For the speech analysis stage, content analysis was used according to the Bardin technique. During the speech analysis process, the following categories were identified: integration, workflow, community and intervention, which generated several subcategories. This analysis made it possible to triangulate the categories and subcategories of both groups. It was clear from the final conclusion of the thesis that teachers and municipal government officials consider that teaching-service integration occurs when teaching is close to health services, together, sharing knowledge, improving workflow and articulating partnerships, enabling education of quality for students and training for health professionals. Although many of the participants still need to understand their role and importance in this integration process. Based on the results obtained, the motivation for the construction of an educational video for teaching-service integration emerges, which suggests that the integration process between an educational institution and a health establishment works properly and brings benefits to both. This video should be used as an innovative way of teaching in permanent education workshops for health workers and teachers.